EFFECTIVENESS OF THE COMBINATION OF DIGITAL AND TRADITIONAL MEDIA IN PRODUCT MARKETING PROMOTION STRATEGIES - Prapanca, Agung; Hidayat, Rahmat (SEAN Institute, 2023)
This research was conducted at the Move Production Printing, which is on Jl. Megawati Gg. Damai Dalam in No. 3g, Medan. The purpose of this study is to find out how effective the combination of digital and traditional media is in product marketing promotion strategies, and what factors influence this effectiveness. the research method used is descriptive qualitative research method. In this study, the authors found that using a combination of digital and traditional media is more effective than relying on only one type of media. The integration of the two types of media enables coordinated and comprehensive promotions, which can increase product attractiveness, expand the reach of the target audience, and increase the effectiveness of promotional messages.